Generating Supplementary Travel Guides from Social Media - YANG, Liu (Institutional Knowledge at Singapore Management University, 2014)
In this paper we study how to summarize travel-related information in forum threads to generate supplementary travel guides. Such summaries presumably can provide additional and more up-to-date information to tourists. Existing multi-document summarization methods have limitations for this task because (1) they do not generate structured summaries but travel guides usually follow a certain template, and (2) they do not put emphasis on named entities but travel guides often recommend points of interest to travelers. To overcome these limitations, we propose to use a latent variable model to align forum threads with the section structure of well-written travel guides. The model also assigns section labels to named entities in forum threads. We then propose to modify an ILP-based summarization method to generate section-specific summaries. Evaluation on threads from Yahoo! Answers shows that our proposed method is able to generate better summaries compared with a number of baselines based on ROUGE scores and coverage of named entities.